(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Substance Use Disorders (SUDs) represent a major public health concern worldwide, contributing significantly to morbidity, mortality, and psychosocial impairment, particularly in low- and middle-income countries. Conventional biomedical models of addiction management primarily focus on detoxification and pharmacotherapy, often neglecting the broader social determinants that influence relapse and long-term recovery. Social psychiatry emphasizes the role of social context, family systems, and community structures in mental health outcomes. Community-based rehabilitation (CBR), endorsed by the World Health Organization, aims to restore dignity, participation, and social inclusion among individuals with chronic health conditions. This prospective longitudinal interventional study evaluated the effectiveness of a community-based social psychiatry rehabilitation model among patients with SUDs admitted to a tertiary care–affiliated rehabilitation centre. Seventy-two adults diagnosed with SUDs were assessed at baseline and at discharge/6-month follow-up using standardized tools for recovery outcomes, psychosocial functioning, and quality of life. Statistically significant improvements were observed in abstinence rates, treatment adherence and quality of life across all WHOQOL-BREF domains, and psychosocial reintegration. Strong family and community support emerged as a significant predictor of sustained recovery. The findings support the integration of social psychiatry principles into addiction rehabilitation services to promote sustainable, dignity-oriented recovery.